Evaluating maternal serum sortilin levels: a potential biomarker for predicting preeclampsia - Gulsan Karabay; Burak Bayraktar; Zeynep Seyhanli; Betul Tokgoz Cakir; Gizem Aktemur; Serap Topkara Sucu; Nazan Vanli Tonyali; Umut Karabay; Dilara Kurt; Ali Turhan Caglar (BMC Pregnancy and Childbirth)
Abstract Objective To determine the role of sortilin in the pathogenesis of preeclampsia by examining serum sortilin levels in maternal blood. Methods This prospective case-control study was conducted from May to November 2023 at the Perinatology Clinic of Ankara Etlik City Hospital. The study cohort was divided into two groups: Group 1 consisted of 44 pregnant women diagnosed with preeclampsia, and Group 2 served as the control group, comprising 44 healthy pregnant women. The groups were matched individually, with controls selected based on similar maternal age and gestational age at the time of sample collection. Results Maternal sortilin levels were significantly elevated in preeclampsia patients compared to controls. Using a cut-off value of > 3.57 ng/mL, sortilin levels could distinguish preeclampsia cases with a sensitivity of 90.9%, a specificity of 45.5%, and an area under the curve (AUC) of 0.679 (p = 0.002). At a cut-off of > 3.57 ng/mL, it was significantly associated with composite adverse neonatal outcomes, with a sensitivity of 89.6%, a specificity of 36.1%, and an AUC of 0.620 (p = 0.045). In addition, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and protein in 24-hour urine, which are important components in the diagnosis and severity of preeclampsia, were significantly correlated maternal blood sortilin levels. Conclusion Our findings indicate that maternal sortilin levels are elevated in patients with preeclampsia compared to those in a healthy pregnant control group. Furthermore, maternal sortilin levels may predict adverse neonatal outcomes. In addition, sortilin levels are correlated key clinical markers of preeclampsia severity.